PEMASANGAN PAPAN NAMA PRAKTIK DOKTER GIGI DILIHAT DARI ASPEK KODE ETIK KEDOKTERAN GIGI DI KABUPATEN SLEMAN - , Erna Fajaryanti, S. H; , Drg. SoetomoNawawi, DPH. Dent.,Sp.Perio (K), ([Yogyakarta] : Universitas Gadjah Mada, 2011)
A research on installing dentist board name, being seen from the aspect of dentist codes has been conducted. The purpose of the research is too see how the dentist, individually or in group,obey the codes specially pertaining to boarding, the research was conducted in Sleman regency. Sampling was based on non random technique to private and group dentist. The data were obtained by interviewing Adang Sudjana Utja, as the head commission of bill drafting on working guidance of MKEKG. Date analizing was based on the technique of on going process. The results of the research have shown that 26,87 % of individual dentist and 70,59 % the ones in group dentist have board name size that do not meet the codes. The individual dentist who meet the codes are 73,13%, in group dentist are 29,41%. The individual dentist who meet the colour of board background are as big as 11,94% the other 88,06% do not. In group dentist, 20% do not meet the codes, 80% do. 7,46% individual dentist are 2,35% the ones in group dentist do not write day and time on the boards, 92, 54% individual dentist and 97,65% in group dentist do. Individualy dentist who do not write titles on boards are 1,49%. The ones not writing licence number 74,63% for individually dentist and 25,37% for in group dentist. The ones who meet the codes are 25,37% for individualy dentist and 15,29% for in group dentist, not writing address are 85,07% for individuals dentist, and 41,18% for in group dentist. The ones do meet the codes are 14,93% for individuals dentist and 58,82% for in group dentist. Having no phone number are 97,01% for individuals dentist and 15,29% in group dentist. Wrong boarding is against the codes, not against the law which its sanction is just administrative.